The electrification of ships using the Northern Sea Route: An approach - Christophe Savard; Anni Nikulina; Céline Mécemmène; Elizaveta Mokhova (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Global warming is causing a major ice retreat from the North Pole. From now on, this retreat allows almost permanent movement between East and West off the coast of the Russian Federation along the Northern Sea Route (NSR). For a long time, navigators have been trying to use this route which significantly reduced the distance between continents. The amount of freight that currently travels on the NSR will inevitably increase in the coming years. To reduce environmental risks, one possible option is not to supply ships with heavy fuel oil. The ships could then be electrically powered and navigate in stages from one port to another along the route to refuel for energy. This electrical energy can be produced on site from renewable energy sources. In this article, a first feasibility analysis is outlined, taking into account the tonnage constraints for navigating on a possible route for the NSR, the cost of energy production and the possible location of several ports of call. Under current economic conditions, the solution would not be profitable as it stands, but should become so at a later stage, which justifies starting to think about a future full electrification of navigation on the NSR, which will also contribute to the economic development of the Russian Federation northernmost regions.
Keywords: 650; Arctic maritime traffic; electrical energy; Northern Sea Route